Cumplimiento de las Buenas Prácticas de Prescripción en el servicio de Pediatría de un establecimiento privado, enero – marzo 2019 - Rojas Ontaneda, Leslie Jenifer (2019)
This research work is a descriptive, cross-sectional and retrospective study, which aims to determine compliance with Good Prescription Practices in the Pediatric Service of a private Establishment, in the period January - March 2019. It was developed as collection instrument a record, in which errors related to patient data, medication data, prescriber data and the most prescribed pharmacological groups are recorded. 365 outpatient prescriptions were evaluated, in which it was found that 100% of the prescriptions contained breach of Good Prescription Practices. Of the total prescriptions with prescription errors in the patient data, 2.74% presented omission of the patient's name and 82.19% presented omission of the patient's age, weight or height. Also, of the total prescriptions with prescription errors of the drug, 87.67% omitted the name DCI, followed by 8.22% who omitted the concentration of the drug and the frequency of administration, 27.40% omitted the route of administration and 71.23% omitted the duration of treatment. Of the total prescriptions with prescription errors in the prescriber's data, 10.96% of the total prescriptions presented illegibility of writing. The most prescribed pharmacological groups were antipyretics and antibiotics with 29.33 and 18.67%, respectively. The average number of prescription medications per prescription was 2.05.